Preformulation Studies of Rosuvastatin - Rajput, Pallavi; Gauniya, Anju (Journal of Drug Delivery and Therapeutics, 2019)
Reliable experimental determination of the solubility of active pharmaceutical ingredients (APIs) in solvents and the correlation for solubility analysis is crucial for the accelerated design and optimization of procedures in the drug industry for isolation, purification and formulation. In this study, the antihypercholesterolemic drug rosuvastatin was evaluated for solubility, effect of pH, compatibity with various exepients. In this research, the rosuvastatin, an antihypercholesterolemic drug was analysed for solubility, pH effect, and compatibility with different excipients. Drug dispersion  subjected to Differential scanning calorimetry and X-ray powder diffractometry.Keywords: Hypercholesterolaemia, HMG-CoA reductase inhibitors, DSC, XRPD